Investigation of Youssef Hussein Bakkar's Critical Views about Arabic Translations of Khayyam's Quatrains Based on Antoine Berman's Theory of Deforming Tendencies - Zahra Bavandpoori; Shahriar Hemmati; Toraj Zeinivand; Ali Salimi (پژوهش‌های ترجمه در زبان و ادبیات عربی, 2021)
Youssef Hussein Bakkar (1942-present) is a writer, researcher, and literary critic among scholars who have attempted to criticize Arabic translations of Khayyam's quatrains through his knowledge of translation techniques. The present study aims to descriptively-analytically criticize his views on these translations based on seven features (rationalization, clarification, theological terms, qualitative ennoblement, quantitative impoverishment, idiom destruction, language system destruction), which are the deforming view of Antoine Bremen (1942-1991), the French pioneer theorist. The findings of the study indicate that Bakkar used his criticism in his reviews and his views are often humorous, devoid of reasoning, and do not follow any particular theory. Adopting a linguistic approach by Bakkar shows that his critique of the method is consistent with the components of Antoine Berman's theory, but Bakkar’s linguistic approach lacks the application of theoretical issues. He does not present his views in a coherent, solidly structured theoretical framework.